Experimental Study on Melt Decontamination of Stainless Steel and Carbon Steel Using Induction Melting - Pengfei Zhao; Wonsub Chung; Mincheol Lee; Seokyoung Ahn (Metals, 2021)
Many nuclear power plants (NPP) facilities have aged and are being dismantled around the world. As a result, large amounts of radioactive metal waste are generated during decommissioning. Carbon steel, stainless steel, and Inconel are the most common metals used in NPP, and radioactive contaminants are mostly accumulated in the corrosion layer. There are various radionuclides, but the main ones are 60Co, 137Cs, 54Mn and 51Cr. 60Co is the major activated corrosion product and responsible for high gamma radiation and longer half-life (5.27 years.) also makes it the most difficult to remove. Therefore, we investigated the melt decontamination characteristics of 60Co by introducing various slags using induction melting for stainless steel and carbon steel. Cobalt plating and cobalt oxide film coatings were used as specimens instead for safety purposes. The amount of cobalt removed from the slag was analyzed by using XRF. About 11% of the cobalt was removed from the contaminated metal due to slag oxide formation. The distribution of cobalt in the melted metal was also almost homogeneous according to the XRD analysis.